Migrasi Suku Dayak Ngaju Dusun Malang dari Juju Lama ke Juju Baru - Areza Saputra Christian; Wingkolatin Wingkolatin; Muhammad Azmi (Yupa: Historical Studies Journal, 2021)
This research focuses on the history of the migration of Dayak Dusun Malang, the migration process, the background of migration and the impact of the migration to the lives of Dayak Dusun Malang. This study uses historical methods with primary data sources obtained from the customary chairman and community leaders, while secondary data is Proleh from the village data and the media of the time relevant to the research. Data collection techniques using interviews, with public figures, observations, reviewing directly the old Juju and documentation, the results showed the reason for the migration carried out by the Dayak Dusun Malang because of the colonialism done by the Dutch and Ngayau. The migration process occurred within 1872-1940 times the existence of a stopover in two places, namely Teluk Punant and Teluk Keriring. The impact of such migrations can be seen in social and economic conditions.